Berger, Monica (audio interview #6 of 6) - Berger, Monica (1891 - ); Briegel, Kaye, interviewer
INTERVIEW DESCRIPTION - This interview was conducted in Berger's home at Leisure World in Seal Beach. 11/7/1979